Study of the quality of honey marketed in the region of Barbacena - MG (Research, Society and Development, 2022)
This study aimed to verify the physicochemical characteristics and the quality of honey produced in the region of Barbacena -MG. The quality of honey samples was determined by evaluating the parameters moisture, reducing sugars, total acidity, hydroxymethylfurfural, diastase activity, water-insoluble solids and ash. Four samples of honey from the region of Barbacena - MG were evaluated, being acquired in local fairs and from street vendors. The analysis results indicated that the samples presented results in accordance with the standards and quality recommended by the Legislation for most parameters, only the acidity of two samples had values above the limit established in the legislation.